Post-Truth And Qur’an: Hacking The Truth Decay Through The Qur’anic Epistemological-Ethical Vision - Afif, Fakhri; Khasri , M. Rodinal Khair; Khasri , M. Ilham Ulul Azmi (Universitas Islam Negeri K.H. Abdurrahman Wahid Pekalongan, 2024)
Post-truth terminology has increasingly enlivened public discussion since it was named as the Word of the Year by The Oxford English Dictionaries in 2016. After giving rise to various discussions, debates, and researches, this terminology was then identified as a serious threat to religious, social, dan political structure of global citizen. The case of alleged religious blasphemy by Basuki Tjahaja Purnama in 2017 and the strengthening of patron-based knowledge authority in the 2019 and 2024 Presidential Election are concrete events which indicate that post-truth and its destructive impacts have spread and reached Indonesia. The strengthening of knowledge patrons implies a condition of unfair construction and distribution of knowledge (epistemic injustice) which includes the testimonial and hermeneutical injustice. Both then lead to the marginalization of a group at a theoretical and practical level. Therefore, post truth urges to be understood as a phenomenon that moves in two spaces, epistemological and ethical, at once. The moral configuration, especially in the context of scriptural morality, which is the reference for life needs to be placed as a part of what is determined by the hermeneutical mode in a broader scope. This article then intends to explore the epistemological-ethical content of the Qur’an by proposing a new reading of the Al-Nur (24):11-20 to deal with the post-truth phenomenon. This study is a qualitative research that based on the literature research and using al-ta’wil al-‘ilmi as a theoretical framework in analyzing research data. The main point that this article wants to emphasize is to show the position, significance, and relevance of the Qur’an in the truth decay era. Through a circular hermeneutical movement that critically integrates the epistemologies of bayānī, ‘irfānī, and burhānī, this article then shows the epistemological-ethical offer of the Qur’an in fighting the post-truth epidemic, namely reaffirmation of the existence of reality along with the essence of universal truth in human knowledge; emphasis on the importance of realizing the complexity of reality, prioritizing rationality, and highlight public virtue; and encouragement to create a relaxed attitude in front of smartphones so that technology can become a vehicle for the actualization of human spirituality. The interconnection of the three epistemological categories above will also be justified by referring to the tension of realism and antirealism in the context of meta-ethics. The implication is that this article also clears up the ambiguity regarding the relationality between the interpreter and the interpretandum (text).